Efeito da desrama sobre o crescimento e a forma de Pinus elliottii Engelm. - Floriano, Eduardo Pagel (2004)
The production of Pinus saw wood accounted for more than 75% of Brazilian total wood production in 2000 and, out of the species from this gender, P. elliottii Engelm. has been one of the most used in commercial plantations. Wood quality in this species is strongly influenced by treatments such as pruning, an operation that brings tree productivity down, yet needed for noble wood production, like the carpentry bound one, which allows for considerably raising wood added value. Aiming at determining the influence of pruning intensity on growth and form of Pinus elliottii Engelm., a test using a random blocks design was set up in a 6- year-old plantation, in Piratini, southeast of Rio Grande do Sul, to which four repetitions and four treatments were applied. The treatments were broken down accordingly their pruning percentage: from 0% (control-not pruned), up to 40%, 60% and 80%-pruning, regarding to the total height of the trees. The operation started off when the trees were 6 years old and underwent a yearly correction as far as turning 6 meters high across all treatments. The results, when the plantation was 15 years old, showed that there was no significant influence of pruning on the mean height, dominant height and mortality rate; diameter and barkless volume were significantly influenced by pruning and yielded the following reductions regarding the control treatment with no pruning: 2% off on the tree diameter and 3.5% off on the tree volume, in the 40%-pruning treatment; 7.5% off on the tree diameter and 15% off on the tree volume, in the 60%-pruning treatment; 13.5% off on the tree diameter and 26.9% off on the tree volume, in the 80%-pruning intensity treatment. Pruning significantly influenced the form of the trees, having been ascertained that pruned treatments give them a conical shape with little trend to a parabolic one, and the control not pruned showed a conical shape with little tendency to a neiloid one. The percentage of clean wood, with no nodes, attained in the three pruned treatments, was alike, averaging out 46% of the total individual barkless volume yielded until 15 years of age. The small reduction in performance shown by the 40%-pruning intensity treatment had no statiscally significant influence on the production, thereby reinforcing literature findings on pruning at this much.